GABAergic Projections to the Oculomotor Nucleus in the Goldfish (carassius Auratus) - Luque, M. Angeles; Torres-Torrelo, Julio; Carrascal, Livia; Torres, Blas; Herrero, Luis (Frontiers in Neuroanatomy, 2011)
The mammalian oculomotor nucleus receives a strong γ-aminobutyric acid (GABA)ergic synaptic input, whereas such projections have rarely been reported in fish. In order to determine whether this synaptic organization is preserved across vertebrates, we investigated the GABAergic projections to the oculomotor nucleus in the goldfish by combining retrograde transport of biotin dextran amine, injected into the antidromically identified oculomotor nucleus, and GABA immunohistochemistry. The main source of GABAergic afferents to the oculomotor nucleus was the ipsilateral anterior octaval nucleus, with only a few, if any, GABAergic neurons being located in the contralateral tangential and descending nuclei of the octaval column. In mammals there is a nearly GABAergic inhibitory inputs; thus, the vestibulooculomotor GABAergic circuitry follows a plan that appears to be shared throughout the vertebrate phylogeny. The second major source of GABAergic projections was the rhombencephalic reticular formation, primarily from the medial area but, to a lesser extent, from the inferior area. A few GABAergic oculomotor projecting neurons were also observed in the ipsilateral nucleus of the medial longitudinal fasciculus. The GABAergic projections from neurons located in both the reticular formation surrounding the abducens nucleus and the nucleus of the medial reticular formation have primarily been related to the control of saccadic eye movements. Finally, all retrogradely labeled internuclear neurons of the abducens nucleus, and neurons in the cerebellum (close to the caudal lobe), were negative for GABA. These data suggest that the vestibuloocular and saccadic inhibitory GABAergic systems appear early in vertebrate phylogeny to modulate the firing properties of the oculomotor nucleus motoneurons.